Influence Of Creative Freedom In Educational Institutions On The Quality Of Education - Tanatova, Dina K.; Yudina, Tatyana N.; Dolgorukova, Irina v; Korolev, Ivan V.; Fomicheva, Tatiana V. (Opción, 2019)
The work analyzes the cause-effect relationships of creative freedom and the educational quality. Freedom of creativity and educational quality is included in a broader concept of well-being – a state of comfort, a person’s satisfaction with their life as a whole, prospects and opportunities in the future. Creative freedom and the quality of education were assessed during a survey of 1,700 respondents. The study revealed that restricted freedom of creativity at universities significantly reduces quality of education. In turn, low quality of edu- cation significantly reduces motivation for creative self-expression.